Spatio-temporal and intraspecific variations in the morphology and morphometry in otoliths of Odontesthes bonariensis (Atheriniformes, Atherinopsidae) - Tombari, Andrea D. (2011)
The morphological and morphometric features of fish otoliths are species–specific. Moreover, some species are known to show intraspecific variations. These could be due to different environmental conditions, but this possibility has scarcely been explored. For the first time, spatio–temporal and intraspecific variations in the shape and size of the otolith of the South American silverside Odontesthes bonariensis (Valenciennes, 1835) are reported. For commercial purposes, this species was introduced from the Chascomús Shallow Lake (Argentina) into other environments with different characteristics. The otoliths used in this study belong to silversides sampled in 2006 from the Chascomús Shallow Lake (Argentina), and in 2006 from the Titicaca Lake (Bolivia) and the Kasumigaura Lake (Japan). Otoliths collected in 1980 from the Chascomús Shallow Lake were also included in the analysis. The species identity of some specimens was subsequently confirmed by molecular techniques. Results of multivariate analyses indicated that there were significant differences in otolith morphology and morphometry among the silverside populations studied, probably related to the environmental conditions where silversides developed.